Psychological Interventions in Improving Positive Body Image in Adolescents: A Systematic Review - Retno Puji Astuti; Rizki Fitryasari; Hendy Muagiri Margono (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Body image is an important issue for adolescents. This is related to the surrounding appearance that is considered attractive by most people where beautiful people are those who have a tall body and white skin. The purpose of this Systematic review is to analyze the effect of psychological interventions on adolescent's body image. Systematic review accessed five electronic databases (Scopus, MEDLINE, CINAHL, Science Direct, and ProQuest). The search was carried out from April to June. 25 articles were analyzed. Most of the psychological interventions provided offline were 16 studies and the rest were through indirect intervention methods. The research design consisted of 17 randomized control trials and 8 studies using quasi-experimental. Two types of psychological interventions can be used as alternatives to enhance and maintain a positive body image: direct psychological intervention and indirect psychological intervention using technology.